Sociological Explanation of the Phenomenon of Honor Killings (for the Sake of Honor) in Khuzestan Province during 2011-2015 - gholamhosein karami; Amir Maleki; Mohammad Javad Zahedi Mazandarani (توسعه اجتماعی, 2019)
The aim of this study was to explain the sociological phenomenon of honor killings in Khuzestan province during the years 2011-2015. This research was conducted using descriptive-survey method. The statistical population consisted of all people who had a criminal case during the years 2011-2015 for the sake of honor killing or deputy in it, in Khuzestan province. According to official statistics, 140 killers and also 140 tribal sheikhs and tribes that the killers were member of them or this phenomenon has happened in their tribes, were chosen. The sampling method was using full scale method. Data collection tools consisted of two types of researcher-made questionnaires which the first questionnaire was used for killers and the second questionnaire was applicated for sheikhs. The coefficient of reliability of their attitude, using Cronbach's alpha method, was 0.89 and 0.81 respectively. Data were analyzed using descriptive and inferential statistics. The findings of the study indicated that among the killers, the variables of tribal dependence, social base, and subculture of violence, attitude towards women and sheikhs support of killers are related with their attitude towards honor killings in Khuzestan province, at P≤0.05. Also, among sheikhs, educational variables, social status, attitude toward women and support for killers are associated with their attitude towards honor killings in Khuzestan province, at P≤0.05.